Illness cognitions and parental stress symptoms following a child’s cancer diagnosis - Lietaviete, Inese; Martinsone, Baiba (Frontiers in Psychology, 2024)
Objective: This research aims to explore parents' cognitive beliefs, specifically illness cognitions, in response to their children being diagnosed with cancer. This study is an initial step toward providing regular psychosocial assessment as a standard for psychosocial care for children with cancer and their families in Latvia.Methods: Data were collected from 120 parents (mostly mothers, n = 109) as an initial evaluation of the psychosocial risks faced by families participating in the support program "Holistic and Multidisciplinary Support for Children with Functional Disabilities and Their Family Members," which was managed by the Children's Hospital Foundation at the Children's Clinical University Hospital in Riga (Latvia) from 2020 to 2023. The patients comprised 66 boys and 54 girls (M age = 7.1, SD = 4.7, range: 0-17 years) with diverse cancer diagnoses. The parents completed the Latvian version of the Psychosocial Assessment Tool (adapted from PAT 3.1 [1]), with five subscales included in the data analysis (Social Support, Child Problems, Family Problems, Stress Reactions, and Family Beliefs). The Family Belief subscale was adjusted specifically to address the unique objectives and research questions of the current study.Results: Significant correlations were found between children's psychological problems (e.g., getting upset about medical procedures, hyperactivity, excessive use of electronic devices, etc.) and parental stress reactions after diagnosis and with self-reported symptoms of anxiety and depression. The associations were statistically significant, even after controlling for sociodemographic and medical factors such as diagnosis. The relationship between children's problems and parental stress reactions was partly mediated by family beliefs about illness. The most informative beliefs associated with parental stress symptoms and the family's psychosocial risk level were identified, and significant results were found according to the main component of beliefs (catastrophic vs. optimistic) that explained 42% of the variance in the Family Beliefs subscale.Implication: Understanding the habitual responses to stress and identifying the thinking patterns of parents that lead to distorted views and maladaptive coping are essential for customizing personalized interventions to enhance treatment compliance. The Latvian version of PAT is a useful psychosocial screening measure in pediatric oncology settings.